Poverty and Wealth in the Polish Cinematography 1945-1989 - Skotarczak, Dorota (Studia Historiae Oeconomicae, 2014)
This article is devoted to poverty and wealth presented in fiction films - both cinema and television - directed in the times of the Polish People’s Republic. Poverty and wealth shown intentionally and unintentionally in these films manifest themselves in many ways. If we want to learn anything about wealth of the society shown in a given movie, a critical approach must be applied.